Operational effectiveness in post-pandemic times : Examining the roles of digital technologies, talent management and employee engagement in manufacturing SMEs - Zahoor, Nadia; Christofi, Michael; Nwoba, Arinze Christian; Donbesuur, Francis; Miri, Domnan (Taylor & Francis, 2022)
This study investigates to what extent the use of digital technologies affects operational effectiveness of emerging market manufacturing small and medium-sized enterprises (SMEs) via talent management and employee engagement in pandemic time. It also examines whether these SMEs’ strategic decision-making speed strengthens the impact of use of digital technologies of ISAs on talent management. Based on human resource and operations management literature, the conceptual model is developed and the mediation and moderation effects are empirically tested between use of digital technologies, talent management, employee engagement, operational effectiveness and strategic decision-making speed. The model is tested using a sample of manufacturing SMEs operating in Pakistan. The findings suggest that talent management mediates the relationship between the use of digital technologies and employee engagement, thereby leading to operational effectiveness. We also found that strategic decision-making speed moderates the relationship between use of digital technologies and talent management.
Keywords: Digital technologies; employee engagement; operational effectiveness; SMEs; strategic decision-making speed; talent management